An investigation into risk and resiliency in gender and sexual minority emerging adults - Scroggs, Barrett (Kansas State University, 2018)
The life-span theoretical framework contends that development occurs throughout the entire life-span and that experiences at one stage of life influence later development (Baltes, 1987). With this in mind, the present studies explore the developmental experiences of gender and sexual minority (GSM) individuals as they make the transition to adulthood. The first study found that overall, there were no major differences in GSM emerging adults’ perceptions of this developmental stage when measured using the Inventory of the Dimensions of Emerging Adulthood (IDEA). The second study situated group identification as a process of identity development and found that identifying with the GSM community was a protective factor for GSM emerging adults. Higher attributions to prejudice were associated with increases in well-being when explained through group identification even though the direct effect was negative. The final study found that, similarly to their heterosexual and cisgender peers, GSM individuals’ self-esteem develops in quadratic fashion over the transition to adulthood and that perceptions of familial understanding in adolescence was significantly associated with both the initial level and the rate of change of self-esteem for this population. Implications for further research are discussed.
Keywords: Emerging adulthood; Lesbian, gay, bisexual, and transgender issues